Endoscopic intervention in second branchial sinus in a 5-month old infant - Munjal, Manish; Munjal, Shubham; Dhillon, Jaspinder K.; Arora, Vineeta; Singh, Swati; Singh, Sandeep; Dhillon, Sukhraj; Kler, Navjot; Chauhan, Rohan; Kaur, Antarpreet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Second branchial sinus anomalies are rare congenital paediatric maladies that arise during intrauterine embryogenesis. A unique case of second branchial arch sinus in a 5-month-old infant, where a minimally invasive transcervical endoscopic intervention was undertaken, is being reported. The presentation was with recurrent discharge from a punctum at the lower lateral aspect of the neck. Global literature on second branchial arch anomalies is reviewed with clinical presentation, imaging, diagnosis, and therapeutic modalities of this rare entity.